Assessing the significance of the economic impact of Marine Conservation Zones in the Irish Sea upon the fisheries sector and regional economy in Northern Ireland. (December 2016) - Moore, Francesca; Lamond, Jessica; Appleby, Thomas
Abstract: This paper highlights the tension between advocacy for 'Blue growth' in maritime policy and efforts to safeguard future economic growth via the Marine Strategy Framework Directive. In 2015, policy-makers withdrew three of four proposed Marine Conservation Zones (MCZs) in the Irish Sea from consideration for designation, due to concerns that they could significantly impact on the fisheries sector in Northern Ireland because they overlap with prawn fishing grounds in the Irish Sea. Although research has quantified the potential impact upon fishing vessels, none has quantified the impact upon the fisheries sector nor assessed the significance of this impact. Arguably, MCZ designations (or lack thereof) based on the 'significance' of an impact require robust underpinning evidence. This paper reports the findings of an Economic Impact Assessment, which has quantified the impact of a decline in landings upon the Northern Ireland fisheries sector and regional economy (data which is currently absent from the evidence base for the MCZ designation process in England). It finds that this will incur job losses in three fishing ports in Northern Ireland, but is unlikely to have a significant impact upon Northern Ireland's fisheries sector and regional economy in terms of jobs and Gross Value Added (GVA). In the worst case, the resulting economic impact is a decrease of £1.05–1.12 m/year GVA in Northern Ireland, which is 1.1% of the contribution of fishing and fish processing to the regional economy. Economic significance assessments, using this methodology, may be useful in supporting the evidence base underpinning MCZ designation and other aspects of marine planning. Highlights: If the four MCZs are designated the key findings are that: ● 2.5% of the value of landings made by Northern Ireland vessels could be lost. ● 7% of all Northern Ireland fishermen could lose their income from fishing (assuming no substitution of fishermen income). ● 4% of the total number of jobs available in the fishing ports would be affected. ● The Northern Ireland economy would lose £1.05–1.12 m/year (GVA) (assuming minimal substitution of prawn supply), which is 1.1% of the contribution of fishing and fish processing to the Northern Ireland economy (of £97.8 m GDP[35] . The actual economic impact will be less than this, accounting for any substitution of income and business adaptation in the fisheries sector.